2022
DOI: 10.3389/fnbot.2022.996685
|View full text |Cite
|
Sign up to set email alerts
|

Application of the robot-assisted implantation in deep brain stimulation

Abstract: IntroductionThis work aims to assess the accuracy of robotic assistance guided by a videometric tracker in deep brain stimulation (DBS).MethodsWe retrospectively reviewed a total of 30 DBS electrode implantations, assisted by the Remebot robotic system, with a novel frameless videometric registration workflow. Then we selected 30 PD patients who used stereotactic frame surgery to implant electrodes during the same period. For each electrode, accuracy was assessed using radial and axial error.ResultsThe average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…1 ). High-resolution post-mortem structural MRI confirmed the accurate location of the DBS electrode within the VLL (average distance between the implantation location and the VLL nucleus over animals:1.7mm +/− 0.4 mm (SE), in line with human studies 25 ). Additionally, we used HDFT between the electrode implantation region and the somatosensory, motor, and pre-motor cortical areas and confirmed that the largest volume of fibers within the stimulation area projected to M1 (on average 55% of the fibers) ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…1 ). High-resolution post-mortem structural MRI confirmed the accurate location of the DBS electrode within the VLL (average distance between the implantation location and the VLL nucleus over animals:1.7mm +/− 0.4 mm (SE), in line with human studies 25 ). Additionally, we used HDFT between the electrode implantation region and the somatosensory, motor, and pre-motor cortical areas and confirmed that the largest volume of fibers within the stimulation area projected to M1 (on average 55% of the fibers) ( Fig.…”
Section: Resultssupporting
confidence: 72%
“…27,28 One study reported their use of a floormounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes). 29 Our meta-analysis found that the floor-mounted systems are more accurate, with a radial target error of 0.90 ± 0.46 mm (n = 1510 electrodes), compared with skull-mounted systems (1.12 ± 0.54 mm, n = 406) (P = .028). There are several different registration methods, including surface registration, frame-based registration, frameless bone fiducial registration, and frameless transient fiducial array registration.…”
Section: Meta-analysismentioning
confidence: 78%
“…27,28 One study reported their use of a floor-mounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes). 29…”
Section: Resultsmentioning
confidence: 99%
“…However, we hypothesize that personal experience is a confounding factor for accuracy and positive diagnostic rates. For this reason, we have organized an expert consensus on biopsy to reduce human factors and bias in biopsy procedure protocols (10,(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%